Contrasting corn yield responses to nitrogen fertilization in southeast coastal plain soils - Raza, Sajjad; Farmaha, Bhupinder Singh (Frontiers in Environmental Science, 2022)
Nitrogen (N) fertilizer recommendations based on yield goals are common and do not consider variability in soil N supply between fields. Nitrogen transformations in soils are dynamic and may vary widely among different soils, climates, cropping systems, and management practices, making it difficult to provide general N recommendation rates for a region, state, or even a county. To optimize N fertilization rates for corn (Zea mays L.), eight field trials were conducted on different fields at the Edisto Research and Education Center of Clemson University in 2018–2021. The soils varied in pH, inorganic N, management practices (irrigate, dryland, cover, and no-cover crop), and climatic conditions (temperature and precipitation). Six nitrogen fertilizer rate treatments were used during 2018 and 2019, eight in 2020, and five in 2021 trials. Test sites were different in each year except in 2021 in which trials were conducted on the same site but were differentiated by multi-species and no-cover crop treatments. Nitrogen fertilizer was applied as a complete one-time dose in all trials in 2018 and 2021 and in several splits in 2019 and 2020. The corn yields generally increased with N fertilization rates; however, a strong variation of up to 4–11 Mg ha−1 existed at each N level among different fields. Based on yield responses, the eight field trials were divided into two groups: low-yielding and high-yielding sites. The low-yielding sites on average produced 3.8 Mg ha−1 of corn, which was 137% less than the corn harvested from high-yielding sites (9.0 Mg ha−1). The agronomic N use efficiency (AgNUE) in high-yielding sites was almost double (32.68 kg kg−1 N) compared to low-yielding sites (17.16 kg kg−1 N), and the differences were even wider for partial factor productivity of N (PFPN). The economic optimum N rate (EONR) remained below 300 kg N ha−1 for all sites with no marked difference among sites. However, relative yield (ratio of corn yield in unfertilized control to the N level giving the highest yield) was comparatively lower in low-yielding sites (29.45%). Baseline inorganic N, pH, and precipitation were identified as the major factors controlling corn yield responses to N fertilization. The yield variations driven by several factors make N management challenging, indicating the need for site-specific N management for corn in the southeast United States.